Complement Nomenclature—Deconvoluted - Bohlson, Suzanne S.; Garred, Peter; Kemper, Claudia; Tenner, Andrea J. (Frontiers in Immunology, 2019)
In 2014, specific recommendations for complement nomenclature were presented by the complement field. There remained some unresolved designations and new areas of ambiguity, and here we propose solutions to resolve these remaining issues. To enable rapid understanding of the intricate complement system and facilitate therapeutic development and application, a uniform nomenclature for cleavage fragments, pattern recognition molecules of the lectin pathway and regulatory proteins of the complement system are proposed, and a standardization of language to designate different activation states of complement components is recommended.